Development of Snakes and Ladders Game Media in Procedural Text Learning for Grade VII Students - Athiyya Azzahra; Rina Devianty (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This research arose due to the lack of understanding and participation of students in learning about procedural texts that still use traditional methods. The purpose of this research is to create a learning media in the form of a snakes and ladders game that focuses on procedural texts and reaches the distance to which the media is feasible, easy to use, and effective. The method applied in this research is Research and Development (RnD) using the ADDIE model which includes five stages: analysis, design, development, implementation, and evaluation. The tools used in the research consist of validation sheets from material experts and media experts, questionnaires to assess teacher and student responses, observation sheets for student activities, and pretest and posttest tests. Data collection was carried out through observation, questionnaires, and tests. To analyze the data, the percentage analysis method was used for validity analysis, practicality, and N-Gain calculations to determine the effectiveness of the media. The research findings show that the snakes and ladders game received a validation percentage from material experts of 90.7% and from media experts of 88.6%, which is categorized as very feasible. The results of the practicality test showed an average percentage of 91% which is categorized as very good. Furthermore, the N-Gain value of 89.7% indicates a high or effective category. Thus, this snakes and ladders learning medium has proven appropriate, practical, and effective for use in textual teaching procedures for seventh-grade junior high school students